Does non-smoker identity following quitting predict long-term abstinence? Evidence from a population survey in England - Tombor, Ildiko (Addict Behav, 2015)
AIMS: ‘Categorical self-labels’ (e.g. thinking of oneself as a smoker or non-smoker) are important aspects of identity that can have a fundamental influence on behaviour. To explore the role identity aspects relating to smoking can play in smoking cessation and relapse, this study assessed the prospective associations between taking on a non-smoker identity following quitting and long-term abstinence. METHODS: A representative sample of 574 ex-smokers in England who quit smoking in the past year was followed-up at three (N = 179) and six months (N = 163). Post-quit identity relating to smoking (‘I still think of myself as a smoker’ or ‘I think of myself as a non-smoker’), and demographic and smoking-related characteristics were assessed at baseline. Self-reported smoking abstinence was assessed at follow-ups. RESULTS: Non-smoker identity was reported by 80.3% (95%CI 76.8–83.4) of recent ex-smokers. Younger age (p = 0.017) and longer abstinence (p < 0.001) were independently associated with a post-quit non-smoker identity. After adjusting for covariates, non-smoker identity (p = 0.032) and length of abstinence at baseline (p < 0.001) were associated with continued abstinence at three month follow-up, and baseline length of abstinence (p = 0.003) predicted continued abstinence at six months. CONCLUSIONS: The majority of people who quit smoking recently consider themselves as non-smokers. Younger people and those who have been abstinent for longer are more likely to take on a non-smoker identity. Ex-smokers who make this mental transition following a quit attempt appear more likely to remain abstinent in the medium term than those who still think of themselves as smokers.